Respuesta :
y-y1=m(x-x1)
y-9=2(x-3) you can use this since its in point-intercept form or continue
y-9=2x-6 then add 9 to each side
y=2x+3
Hope this helps and is Correct!
y-9=2(x-3) you can use this since its in point-intercept form or continue
y-9=2x-6 then add 9 to each side
y=2x+3
Hope this helps and is Correct!
ANSWER
[tex]y - 9 =2(x - 3)[/tex]
l
Or
[tex]2x - y + 3 = 0[/tex]
Or
[tex]y = 2x + 3[/tex]
EXPLANATION
The given line has slope,
[tex]m = 2[/tex]
and
[tex](3,9)[/tex]
We can find the equation in the point slope form, which is given by,
[tex]y-y_1=m(x-x_1)[/tex]
We substitute the point and slope to get,
[tex]y - 9 =2(x - 3)[/tex]
We can also simplify further to get,
[tex]y - 9 = 2x - 6[/tex]
We make y the subject to get,
[tex]y = 2x - 6 + 9[/tex]
[tex]y = 2x + 3[/tex]
This is called the slope intercept form.
We could also write in standard form to get
[tex]2x - y + 3 = 0[/tex]
Or
[tex]2x - y = - 3[/tex]
[tex]y - 9 =2(x - 3)[/tex]
l
Or
[tex]2x - y + 3 = 0[/tex]
Or
[tex]y = 2x + 3[/tex]
EXPLANATION
The given line has slope,
[tex]m = 2[/tex]
and
[tex](3,9)[/tex]
We can find the equation in the point slope form, which is given by,
[tex]y-y_1=m(x-x_1)[/tex]
We substitute the point and slope to get,
[tex]y - 9 =2(x - 3)[/tex]
We can also simplify further to get,
[tex]y - 9 = 2x - 6[/tex]
We make y the subject to get,
[tex]y = 2x - 6 + 9[/tex]
[tex]y = 2x + 3[/tex]
This is called the slope intercept form.
We could also write in standard form to get
[tex]2x - y + 3 = 0[/tex]
Or
[tex]2x - y = - 3[/tex]